ISLAM AND CAPITALISM: THE DYNAMICS OF RELIGION AND CONTEMPORARY INDONESIAN WORK ORIENTATION - Husnul Khitam (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
Indonesia is the world's fourth most populous nation, with about 265 million people, and has the most significant number of adherents to Islam. The country also was well known as one of the new tigers of Southeast Asia in the mid-80s with high economic development. The impressive economic growth at an average level of 5 percent, a low rate of inflation at 2.36, the rose of consumption growth to 5.1 percent, the rapid decline of poor people, and the low Gini ratio index at 0.382 show how vital Indonesia as an exemplar of the growth of capitalism in the global south. The fact that the most populous Muslims are spread widely in Southeast Asia and Indonesia would be the best example of how capitalism and religion play their role along with their cultural and social characteristics. Therefore, the main aim of the following study is to analyze contemporary Indonesia through the lenses of classical sociology theory, especially to reveal the fundamental question of how capitalist, religious, and work-oriented Indonesian society is? Within Indonesia's contemporary context and the tension between capitalism and religion, this study shows the relationships and dynamics between the two and forms another kind of capitalism.